Early Diagnosis of Upper Eyelid Pyoderma Gangrenosum Using the PARACELSUS Score and Tissue-Sparing Management With Adjunctive Hypochlorous Acid Therapy: A Case Report - Anil Akdeniz; Görkem Polat; Safiye Aktaş; Meryem Altin Ekin (Ophthalmic Plastic & Reconstructive Surgery, 2026)
Pyoderma gangrenosum (PG) is a rare neutrophilic dermatosis that may cause rapid tissue destruction when it involves the periocular region. We report a 17-year-old patient with ulcerative colitis who developed progressive upper eyelid ulceration initially treated as preseptal cellulitis and later suspected necrotizing infection. Despite broad-spectrum antibiotics, the lesion worsened. Clinical findings, sterile cultures, associated cutaneous lesions, and a PARACELSUS score of 17 strongly supported the diagnosis of PG, prompting immediate systemic corticosteroid therapy before histopathologic confirmation. Adjunctive wound care included topical hypochlorous acid therapy and ophthalmic antibiotic ointment. Histopathology subsequently confirmed PG. Complete re-epithelialization was achieved within 3 weeks without eyelid malposition, functional sequelae, or recurrence during 8 months of follow-up. This case highlights the value of the PARACELSUS score in facilitating early diagnosis of periocular PG and supports prompt tissue-preserving management to prevent irreversible eyelid damage.